2009
DOI: 10.1681/asn.2008010117
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Urinary Haufen Accurately Predicts Polyomavirus Nephropathy

Abstract: There are no accurate, noninvasive tests to diagnose BK polyomavirus nephropathy, a common infectious complication after renal transplantation. This study evaluated whether the qualitative detection of cast-like, three-dimensional polyomavirus aggregates ("Haufen") in the urine accurately predicts BK polyomavirus nephropathy. Using negative-staining electron microscopy, we sought Haufen in 194 urine samples from 139 control patients and in 143 samples from 21 patients with BK polyomavirus nephropathy. Haufen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 32 publications
3
102
0
Order By: Relevance
“…In the context of incompatible transplantation, a cohort at increased risk for rejection, the ability to clearly differentiate between the two histopathologic diagnoses is crucial. In a retrospective analysis of compatible kidney transplant recipients, Singh et al (35) reported excellent ability of cast-like, three-dimensional polyomavirus aggregates (termed Haufen crystals) to qualitatively predict the presence of BKVAN (97% and 100% positive and negative predictive values), a putative future option.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of incompatible transplantation, a cohort at increased risk for rejection, the ability to clearly differentiate between the two histopathologic diagnoses is crucial. In a retrospective analysis of compatible kidney transplant recipients, Singh et al (35) reported excellent ability of cast-like, three-dimensional polyomavirus aggregates (termed Haufen crystals) to qualitatively predict the presence of BKVAN (97% and 100% positive and negative predictive values), a putative future option.…”
Section: Discussionmentioning
confidence: 99%
“…Other markers associated with PyVAN are BKV VP1 mRNA of >6 log copies/ng total urine RNA (64) or the detection urine PyV aggregates by electron microscopy (65). PyVAN (42,44,53,66 (83,84), while others report no demonstrable benefit (54,(85)(86)(87).…”
Section: Diagnosis Of Pyvanmentioning
confidence: 99%
“…Haufen, a recently described entity, are discrete cast-like three-dimensional viral aggregates detectable by negative staining electron microscopy. The detection of Haufen aggregates was reported to be associated with BKVN to a high degree of sensitivity and specificity, such that PPV and NPV are both above 97% [49,50]. These initial studies need to be confirmed in larger series.…”
Section: Diagnosismentioning
confidence: 94%